Quercetin prevents 2,3,7,8-tetrachlorodibenzo-p-dioxin-induced testicular damage in rats - Ciftci, O.; Aydin, M.; Ozdemir, I.; Vardi, N. (Wiley, 2012)
The protective effect of quercetin on 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-induced testicular damage in rats was investigated. Twenty-two rats were equally divided into four groups; first group was kept as control and given corn oil as carrier. In second group, TCDD was orally administered at the dose of 2 mu (kg week)-1 for 60 days. In third group, quercetin was orally administered at the dose of 20 mg (kg day)-1 by gavages, and in fourth group TCDD and quercetin were given together at the same doses. Although TCDD increased the formation of thiobarbituric acid reactive substances (TBARS) significantly, it caused a significant decline in the levels of glutathione (GSH), catalase (CAT), GSH-Px and CuZn-Superoxide Dismutase (CuZn-SOD) in rats. In contrast, quercetin significantly increased the GSH, CAT, GSH-Px and CuZn-SOD levels but decreased the formation of TBARS. In addition, sperm motility, sperm concentration and serum testosterone levels were significantly decreased but abnormal sperm rate and testicular damage were increased with TCDD treatment. However, these effects of TCDD on sperm parameters, histological changes and hormone levels were eliminated by quercetin treatment. Our results show that administration of TCDD induces testicular damage (oxidative stress, testes tissue damage, serum hormone level and sperm parameters), and quercetin prevents TCDD-induced testicular damage in rats. Thus, quercetin may be useful for the prevention and treatment of TCDD-induced testicular damage.
Keywords: 2; 3; 7; 8-TCDD; Quercetin; testicular damage; testosterone